Answer:
hlo ji good evening ji please follow me
x = 64°
Step-by-step Explanation
x = 1/2[(360° - 2*58°)-2*58°]
x = 1/2[(360° - 2*58°) - 2*58°]
x = 1/2[(360° - 116°) - 116°]
x = 1/2[244° - 116°]
x = 1/2[128°]
x = 64°
Answer:-45
Step-by-step explanation:this is how I do it: draw a line in the middle of the equal sign. Now its split in two parts. Do the opposite operation on the left side, so minus 6 from the left AND the right. Now it equals to y/3 = -15. Now times each side by 3 so the y stands alone. -15 times 3 equals -45. Y = -45. Sorry it's kinda hard to explain!
Answer:
if ma and m id black life matters if balck
Answer:
Sequence 1
Step-by-step explanation:
<u>You need to find the difference between term - the nth term.</u>
<u>The difference / nth term has to to -1/2 (-0.5)</u>
Sequence 1:
-6 * -0.5 = 3 * -0.5 = -3/2 (-1.5) * -0.5 = 3/4 (0.75) * -0.5 = -3/8 (-0.375)
Sequence 2:
4 * -2 = -8 *-2 = 16 * -2 = - 32 * -2 = 64
Sequence 3:
-1/3 ÷ 2 = -1/6 ÷ 2 = 12 ÷ 2 = 24 ÷ 2 = 48
Sequence 4:
400 ÷ -2 = -200 ÷ -2 = 100 ÷ -2 = -50 ÷ -2 = 25
The only sequence with a common ratio of -1/2 is Sequence 1.